Consumption of Ultraprocessed Foods in a Sample of Adolescents With Obesity and Its Association With the Food Educational Style of Their Parent: Observational Study - Sylvie Borloz; Sophie Bucher Della Torre; Tinh-Hai Collet; Corinne Jotterand Chaparro (JMIR Publications, 2021)
BackgroundBoth parental education and the food environment influence dietary intake and may therefore contribute to childhood obesity. ObjectiveWe aimed to assess the consumption of ultraprocessed foods (UPFs) in a convenience sample of adolescents with obesity and to determine its association with the food educational style of their parent. MethodsThis observational study included 24 participants, 12 adolescents (8 boys and 4 girls) aged from 12 to 14 years and their 12 parents, who were followed in a specialized pediatric obesity clinic in the French-speaking part of Switzerland. The adolescents were asked to take a photograph with a smartphone application of all meals and beverages consumed in their daily routine over 14 consecutive days. They evaluated their parent's food educational style using the Kids' Child Feeding Questionnaire. The parent who was present at the study visits also completed the Feeding Style Questionnaire. A dietitian analyzed the pictures to extract food group portions and to identify UPFs using the NOVA classification. A nonparametric statistical test was used to investigate associations between UPF intake and food educational style. ResultsOverall, the adolescents had unbalanced dietary habits compared to national recommendations. They consumed an insufficient quantity of vegetables, fruits, dairy products, and starchy foods and an excessive amount of meat portions and sugary and fatty products compared to the current Swiss recommendations. Their consumption of UPFs accounted for 20% of their food intake. All adolescents defined their parent as being restrictive in terms of diet, with a mean parental restriction score of 3.3±SD 0.4 (norm median=2.1). No parent reported a permissive food educational style. A higher intake of UPFs was associated with a lower parental restriction score (P=.04). ConclusionsDespite being followed in a specialized pediatric obesity clinic, this small group of adolescents had an unbalanced diet, which included 20% UPFs. The intake of UPFs was lower in participants whose parent was more restrictive, suggesting the importance of parents as role models and to provide adequate food at home. Trial RegistrationClinicalTrials.gov NCT03241121; https://clinicaltrials.gov/ct2/show/NCT03241121